The impact of natural disasters on rural household wealth: Micro evidence from China - Wu, Shaoyong; Zhang, Rui; Wang, Chuncao; Feng, Dawei (Frontiers in Environmental Science, 2022)
Economic inequality includes not only income inequality, but also wealth inequality. Compared with income inequality, wealth inequality is a more comprehensive reflection of household economic situations. Examining the factors that influence rural households’ wealth facilitates enhancing poor households’ happiness, improving their overall welfare, and narrowing the wealth gap between different households. Thus, this study analyzed data from the China Family Panel Survey (CFPS) using multiple linear regression and propensity score matching methods to examine the impact of natural disasters on rural household wealth. Our findings showed that natural disasters have a significant negative impact on rural household wealth, with a medium- to long-term effect. Additionally, the heterogeneity analysis indicated that natural disasters have a greater effect on the wealth of larger households and households with high-consumption levels. Mechanism results suggest that natural disasters affect rural household wealth by reducing individuals' income and their physical and mental health.